Transcriptomic profiling reveals RetS-mediated regulation of type VI secretion system and host cell responses in Pseudomonas aeruginosa infections - Wu, Yinglin; Huang, Shan; Zhang, Kai; Shen, Yangcheng; Zhang, Shebin; Xia, Haining; Pu, Jieying; Shen, Cong; Chen, Cha; Zeng, Jianming (Frontiers in Cellular and Infection Microbiology, 2025)
Pseudomonas aeruginosa is a major opportunistic pathogen that causes chronic infections, particularly in patients with cystic fibrosis and chronic obstructive pulmonary disease (COPD). The type VI secretion system (T6SS) is a primary virulence factor of P. aeruginosa in chronic infections. The objective of this study was to elucidate the regulatory mechanisms and pathogenic effects of the T6SS during P. aeruginosa infection, utilizing transcriptome sequencing and functional assays. We found that T6SS expression is elevated in P. aeruginosa isolated from chronically infected patients. Deletion of the retS gene activates P. aeruginosa PAO1 T6SS while repressing T3SS in vitro. Bacterial and cellular transcriptome sequencing analyses showed that T6SS genes were upregulated, while T3SS genes were downregulated in the ΔretS mutant. Additionally, the expression levels of the fimbriae gene cupC, the histidine phosphotransfer protein hptC (PA0033), and the transcription factor PA0034 were significantly increased. Subsequent experiments revealed that adhesion mediated by cupC enhances the contact-killing activity of the T6SS. Deletion of the hptC-PA0034 operon results in the down-regulation of cupC expression. The ΔretSΔcupC and ΔretSΔhptC-PA0034 mutants exhibited reduced cytotoxicity compared to the ΔretS mutant, similar to the ΔretSΔclpV1ΔclpV2 mutant. The ΔretS infection increased cell death, inflammatory factors (IL-1β, IL-6, TNF-α), and reactive oxygen species compared to a T6SS-inactive strain. Importantly, our study demonstrates that the T6SS activates the PDE4C pathway in epithelial cells, leading to significant cellular alterations. The application of PDE inhibitors effectively mitigates cell damage and inflammatory responses. These findings highlight the critical role of T6SS in modulating host cell signaling and suggest potential therapeutic strategies for conditions associated with T6SS-mediated inflammation.